Starting Point of Modernization of Islamic Education: Analyasis of Internal and External Factors - M. Saifuddin Yulianto (Didaktika Religia, 2017)
The stagnation in the field of Islamic education and intellectualism in the era of Islamic decline is allegedly derived from the gradual dicline of the religious sciences, because of its isolation from the intellectual life that eventually died. The determinants of the importance of modernization of Islamic education in the form of internal factors include: the existence of an Islamic education system that is accommodative to the changing times. Meanwhile, the external factors that are urgent to immediately modernization of Islamic education is to catch up with other nations.